Europe in the Age of Post-Truth Politics
XVII, 259 p. 5 illus., 2 illus. in color.
Keywords: This open access book is the product of three years of academic research that has been carried out in the EU-funded Jean Monnet Network on “Post-Truth Politics, Nationalism and the Delegitimation of European Integration” since 2019. Drawing on the multidisciplinary expertise of the network’s members, the book explores the impact of the phenomenon of post-truth politics on European integration and the European Union. It places particular emphasis on how post-truth politics has played out in the public sphere and asks what impact the phenomenon has had on public deliberation, but reflects also on its implications for democracy in a wider sense. This book is primarily written for audiences with an interest in politics and policy making, including academics, policy makers and civil-society actors. Thanks to its accessible style, the book should however also be an asset to wider audiences. Maximilian Conrad is Professor of Political Science at the University of Iceland. Guðmundur Hálfdanarson is Professor of History at the University of Iceland. Asimina Michailidou is Senior Researcher at the ARENA Centre for European Studies, University of Oslo, Norway. Charlotte Galpin is Associate Professor of German and European Politics at the University of Birmingham, UK. Niko Pyrhönen is Researcher in the Faculty of Theology, University of Helsinki, Finland. .